CONSTRUCTIVIST THEORY AND A TEACHING AND LEARNING CYCLE IN ENGLISH - Ratna Rintaningrum (Institut Teknologi Sepuluh Nopember, 2008)
Today the philosophy of constructivism has been spread through the world; and it seems that this philosophy has become the most popular in education. This might be because the concepts of this philosophy have been supported by the advance of digital technology which offers large variety of activities, in which the activities involve those required by constructivism.